Rhizospheric Bacillus-Facilitated Effects on the Growth and Competitive Ability of the Invasive Plant Ageratina adenophora - Du, Ewei; Chen, Yaping; Li, Yahong; Sun, Zhongxiang; Gui, Furong (Frontiers in Plant Science, 2022)
The rhizospheric microbial community affects the population establishment of invasive plants in introduced areas, among which Bacillus has numerous functions in promoting plant growth. This study isolated and enriched the Bacillus community in the rhizospheric soil of the invasive plant Ageratina adenophora and the native accompanying plant Rabdosia amethystoides. The effects of these rhizospheric Bacillus communities on the growth and competition of A. adenophora and R. amethystoides were evaluated in pot experiments. The results showed that the number and diversity of Bacillus in the rhizospheric soil of A. adenophora were higher than those of R. amethystoides (A. adenophora: 122 strains in soil, 16 Bacillus taxa; R. amethystoides: 88 strains in soil, 9 Bacillus taxa). After Bacillus inoculation of A. adenophora in a pot experiment, Bacillus idriensis, Bacillus toyonensis and Bacillus cereus were accumulated in the rhizospheric of A. adenophora, which significantly increased the nitrate nitrogen (NO3−-N) content in the soil and the total carbon and nitrogen concentrations in A. adenophora in the mixed treatment. The selective accumulation of Bacillus enhanced the competitive advantage of A. adenophora over the native accompanying plant; the corrected index of relative competition intensity of A. adenophora-inoculated Bacillus reached double that of the uninoculated treatment, and the growth of native plants was greatly suppressed under mixed planting. Our study confirmed that invasion of A. adenophora can lead to the accumulation of specific Bacillus taxa in the rhizospheric soil, which in turn can increase the competitive advantage of A. adenophora.